Analisis Strategi Pengembangan Pada Baitul Maal Wat Tamwil (Bmt) Amal Mulia Suruh Kabupaten Semarang - , Amprianto; , M. Farid Wajdi, Ph.D; , Dr. Anton Agus Setyawan, SE,. M.Si, (2016)
This research analyze the development of strategy in the Islamic Micro-finance Institution. The various factors of this research analyzes are internal and external environment which is used as the basic of developing strategies that can be applied at BMT (Baitul Maal Wat Tamwil) Amal Mulia at Suruh Semarang. The internal factors as strength are: 1) the high level of familiarity management and official employees on clients and society, 2) the strategic location, 3) BMT Has a good brand image in the society, 4) the effectively of using financial capital, 5) the satisfaction clients of products offered. The weaknesses of internal factors are: 1) the firmness employees in dealing of disobedient client, 2) BMT Has a limited building, 3) there is overlapping job division, 4) the BMT has no much financial capital, 5) some employees cannot use a given product. The external factors of opportunities are: 1) there is lending from the government or other companies, 2) most of the societies are traders, 3) BMT system adopted for the profit sharing so resilient to the global crisis, 4) the BMT supported by government regulations, 5) technology information used to support the online service programs. The threats external factors are: 1) retrieval of costumer funds is caused by negative issues, 2) increasing fuel can be influence operating costs of BMT, 3) the government regulations which are usually change, 4) the less of perceptions and knowledge about the shariah concept, 5) cost of acquisition and development online system are high. Furthermore the analyzes or internal and external factors obtained three strategic priorities are: 1) cooperating with all partners to obtain financial support, 2) need to intensive pressuring market, 3) improving the quality of internal services through trainings for a variety of operational areas. Keyword: BMT, External Environment, Internal Environmrent, Strength, Weakness, Opportunity, Threat (SWOT).